Ahmadiyah dalam Pusaran Sejarah: Analisis Kritis Terhadap Doktrin dan Pengaruhnya - Nur, Zulfikah; Amri, Muhammad; Aderus, Andi (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to find out the history of Ahmadiyya through a critical analysis of its doctrine and influence. This research is research using a Historical approach that relies on four main activities, namely Heuristic, Interpretation, Criticism, and Presentation. The data collection technique is through archival and literature studies and then uses interview techniques and field studies as a comparison. The findings of this analysis are that the entry of Ahmadiyah Qadian into Indonesia began because of a request from Indonesian youth who were studying in Qadian, namely Abu Bakar Ayyub, Zaini Dahlan, Ahmad Nuruddin, and other friends, the majority of whom were from West Sumatra. As a da'wah movement, Ahmadiyah emphasizes the spiritual aspect of Islam, which is mahdiist, namely the fact that Mirza Ghulam Ahmad is al Mahdi who carries out the mission of eliminating darkness and creating peace in the world. In addition, the Ahmadiyya movement positions itself as a reform movement that aims to restore Muslims to the root of Islamic truth, based on the Quran, hadith, and spread it according to the teachings of Mirza Ghulam Ahmad based on the revelations he received